Prevalence and predictors of gender-based violence among Wolkite University female students, southwest Ethiopia, 2021: Cross-sectional study - Workye, Haile; Mekonnen, Zebene; Wedaje, Wesen; Sitot, Aregash (Frontiers in Reproductive Health, 2023)
Background: - Gender-based violence is an important gender consideration that needs to be taken into serious attention when identifying gender-related gaps done to a person because of their gender. Violence against women could result in psychological and physical adverse outcomes. Therefore; this study was to assess the prevalence and predictors of gender-based violence among female students at Wolkite University, Southwest, Ethiopia, 2021. Method: - An institutional-based cross-sectional study was conducted on 353 female students and the students were selected by systematic sampling.. Data were checked for completeness and entered into epi-data version 3.1 and then exported to SPSS version 23 for further analysis. Binary and multivariable logistic regressions were employed to determine the prevalence and predictors of gender based violence. Result: In this study, the overall prevalence of gender-based violence among female students during their lifetime was 46.2%, 56.1% physical violence, and 47.0% was sexual violence. The prevalence of gender-based violence of female students was 44.8% before joining University, 28% was since joining University, and 18.7% was in this year In this study, educational level of female students 2nd year (AOR= 2.56 (95% CI, 1.06-6.17)), married or living with male partner (AOR=3.35 (95% CI, 1.07-10.5), educational status of the father (AOR=15.46 (95% CI, 5.204-45.39)), lifetime drinking habit(AOR=2.53(95% CI,1.21-6.30) and freely discuss with families (AOR=2.48 (95% CI), 1.27-4.84) were significantly associated and predictors of gender-based violence among female university students. Conclusions and recommendations: The result of this study shows that the prevalence of gender-based violence was very high so university and concerned bodies should work hard and study further about female students’ awareness about their legal rights concerning sexual violence. Keyword: - Gender-Based Violence; physical violence; sexual violence, Wolkite, Ethiopia